Low plasma protein nitrotyrosine levels distinguish primary Raynaud's phenomenon from scleroderma. Issue 7 (24th November 2005) - Kingdon, E J; Mani, A R; Frost, M T; Denton, C P; Powis, S H; Black, C M; Moore, K P
Abstract : Objective: To investigate the hypothesis that increased formation of reactive nitrogen species may contribute to the vascular pathology that develops in patients with connective tissue disease such as scleroderma. Patients and methods: The level of protein-bound nitrotyrosine in plasma was measured by stable isotope dilution gas chromatography/negative ion chemical ionisation mass spectrometry in 11 patients with primary Raynaud's phenomenon, 37 with scleroderma, 13 with chronic renal impairment, and in 23 healthy controls. Results: Plasma protein-bound nitrotyrosine was markedly decreased in patients with primary Raynaud's phenomenon (mean (SEM) 0.60 (0.06) ng/mg dry protein) compared with patients with scleroderma (1.78 (0.21) ng/mg protein), chronic renal impairment (1.42 (0.17) ng/mg protein) or healthy controls (1.63±0.15 ng/mg protein, ANOVA p<0.001). Conclusion: These data suggest that there is decreased nitration of plasma proteins, or increased degradation of nitrated proteins from the circulation of patients with primary but not secondary Raynaud's phenomenon.